Isolation of Antibiotic-Resistant Bacteria from Touch Screen Mobile Phones - Shee, Hui Ping (2016)
Nowadays, people are inevitable indispensably to mobile phones including touch screen mobile phones. Although touch screen mobile phones offer a lot of advantages such as rapid communication, they are also a reservoir for bacteria transmission. This study has identify the counts and types of bacteria contaminating touch screen mobile phones used by students of INTI International University. Forty-three touch screen mobile phone samples were collected. Along with the questionnaire, an area of 3cm on the surface of the touch screen mobile phones had been aseptically rubbed over using the sterilized cotton swabs. Samples were cultured to obtain pure isolates. The percentage of the purpose of bacterial on touch screen mobile phones was 100% and 79 isolates were found. The pure isolates were identified through some biochemical test including gram staining, catalase test, oxidase test and IMViC test. Sixty-nine isolates (87.34%) were gram positive whereas 10 isolates (12.66%) were gram negative. Besides, the pure isolates were streaked on MSA and MacConkey Agar in order to differentiate different type of bacteria such as S. epidermidis that produced pink colonies on MSA and S. aureus that produced yellow colonies on MSA. The identification of isolates were done by using Bergey’s Manual (Bergey & Holt, 1994). The most common isolate in this study was S. epidermidis and followed by S. aureus. Therefore, the pure cultures were subjected to antibiotic susceptibility test to investigate their antibiotic susceptibility profiles. Forty-one isolates showed antibiotic resistance, 32 of them were gram positive and 9 of them were gram negative. Among the 32 gram positive antibiotic-resistant isolates, 15 of them were oxacillin-resistant while 17 of them were clindamycin-resistant. Among 20 (28.99%) possible S. aureus, four (5.8%) of them showed oxacillin resistance and eight (11.60%) of them showed clindamycin resistance. The four possible S. aureus that showed oxacillin resistance were grown on Brilliance MRSA 2 Agar, but only one grew as blue colonies, indicating only one of them was MRSA. Among 21 (30.43%) possible S. epidermidis, 11 of them were oxacillin-resistant and 9 of them were clindamycin-resistant. The oxacillin-resistant S. epidermidis might be the possible MRSE. For the gram negative isolates, one (10%) possible Neisseria species was chloramphenicol-resistant. Three (30%) possible Salmonella species were amikacin-resistant and four (40%) of them were chloramphenicol-resistant.